Selective oxidations over zeolite- and mesoporous silica-based catalysts: selected examples - Ratnasamy, Paul; Srinivas, Darbha (Catalysis Today, 2009)
Selective oxidation of hydrocarbons/terpenes in the liquid phase are reported over three categories of zeolite- and mesoporous silica-based catalysts: (1) transition metal complexes (metal phthalocyanines, copper acetate dimers and Co/Mn acetate trimer) encapsulated in zeolite-Y, (2) transition metal complexes (Mn-Salen), grafted on SBA-15, and (3) transition metal ions in framework positions of zeolites and mesoporous molecular sieves like Ti-silicates. Upon heterogenization, the metal complexes exhibited enhanced catalytic acitivity/selectivity. The causes for the enhanced catalytic activity/product selectivity have been explored. Dimer formation (copper acetate) or geometric distortion in the zeolite cavities (metal phthalocyanines) and consequent changes in energy levels and redox potentials are shown to modify the catalytic activity (in the selective oxidation of hydrocarbons) of the encapsulated metal complexes. In the case of Mn-Salen grafted on SBA-15, increasing the acidity of the siliceous surface (by -SO(3)H groups, for example) leads to a more facile reduction of the Mn ions and, thereby, enhanced catalytic activity in the selective epoxidation of limonene. When Ti ions are introduced in framework positions, reactive metal-oxo species are formed on contact with H(2)O(2) or O(2), Which influence the mode of O-O cleavage (heterolytic/homolytic) and product selectivity. The structure-function relationships in these catalysts are reported. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Mn-Salen; Oxidation of hydrocarbons and limonene; Reactive oxo species; Selective oxidation; Titanosilicates; Zeolite-encapsulated metal complexes

Synthesis of framework Ti-substituted, 3-D hexagonal, mesoporous Ti-SBA-12 for selective catalytic oxidation - Kumar, Anuj; Srinivas, Darbha; Ratnasamy, Paul (Chemical Communications, 2009)
Framework Ti-substituted, 3-D hexagonal mesoporous, Ti-SBA-12, obtained for the first time by direct hydrothermal synthesis, oxidises bulky molecules such as cyclohexene and cyclooctene to the epoxides with >96% selectivity at high conversion levels (>60%).